Does Fear of Crime Moderate the Relationship Between Low Self-Control and Victimization? An Empirical Study - Guedes, Inês Sousa (European journal on criminal policy and research, 2025)
Taking into consideration the framework of the general theory of crime, research has been exploring the role of low self-control in the explanation of both crime perpetration and personal victimization. Moreover, while several studies have been analysing the role of victimization experiences in the fear of crime, less is known about how an individuals’ fear of crime influences the likelihood of being victimized. Therefore, using a sample of 243 individuals (55.6% women) from the University of Porto, through a self-reported survey, we tested (i) the effects of low self-control on victimization and (ii) the moderating role of fear of crime on the relationship between self-control and victimization. Results showed that low self-control was positively correlated with victimization. It was observed that fear of crime moderated the effect of low self-control on victimization, thus suggesting that the relationship between low self-control and victimization is not observed when fear of crime is high. Implications of the results are discussed.